Vyhledávací studie obchvatu obce Výšovice - Tichý, Václav (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2023)
The aim of this bachelor thesis is to prepare a research study of a bypass of the Výšovice village. Výšovice is located in the Region of Olomouc, 7 km south of Prostějov. The bypass is designed as S7,5/90 and connects to the existing road II/433. Three options are proposed for the bypass, options are subsequently compared and one of them is elaborated in more detail. The construction of the bypass will reduce the traffic intensity in the village.
Keywords: Obchvat; Vyhledávací studie; Location study; Výšovice; Bypass